(untitled) - Brozo, William G. (New York, 2011)
This accessible guide defines RTI and explains why and how it is considered a viable intervention model for adolescent readers. Drawn from real secondary school cases demonstrating tiered interventions, the text includes evidence-based strategies, discussion questions for each case study, and prompts that foster critical thinking.
Keywords: Education, Secondary,School improvement programs,Khắc phục dạy học,Giáo dục, Trung học,Chương trình cải tiến trường học,Remedial teaching; United States,United States,Hoa Kỳ,Hoa Kỳ,Hoa Kỳ,United States